1995
DOI: 10.1161/01.str.26.5.878
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Studies of Extracellular Metabolites in the Striatum After Distal Middle Cerebral Artery Occlusion in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: Our study demonstrated that changes of neurotransmitters in the lateral part of the striatum after MCA occlusion differed from those in the medial part. These results suggest that excessive release of glutamate and dopamine is related to delayed neuronal damage that occurs in the lateral part of the striatum in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…30 Moreover, in the present study the extracellular concentrations of glutamate and aspartate are 3-fold lower and those of GABA and taurine 10-fold lower than they are 2 hours after probe implantation. 31 The increase in amino acid transmitters and adenosine found in our experiments confirms the increase observed by several authors in both the cortex 17,19 -21,32 and striatum 17,18,22 of anesthetized animals after MCAO. In agreement with them, we found that GABA shows the largest outflow increase of the amino acids.…”
Section: Advantages Of the Intraluminal Approach Of Mcao In Combinatisupporting
confidence: 90%
See 2 more Smart Citations
“…30 Moreover, in the present study the extracellular concentrations of glutamate and aspartate are 3-fold lower and those of GABA and taurine 10-fold lower than they are 2 hours after probe implantation. 31 The increase in amino acid transmitters and adenosine found in our experiments confirms the increase observed by several authors in both the cortex 17,19 -21,32 and striatum 17,18,22 of anesthetized animals after MCAO. In agreement with them, we found that GABA shows the largest outflow increase of the amino acids.…”
Section: Advantages Of the Intraluminal Approach Of Mcao In Combinatisupporting
confidence: 90%
“…A different factor may be an increase in glutamate metabolism by astrocytes, observed after ischemia in vivo. 49 Unlike the excitatory amino acids, the levels of the inhibitory amino acids GABA and taurine remained high after permanent MCAO, in agreement with the results of Shirotani et al, 22 and are still high 4 hours after MCAO. Two mechanisms may be invoked to explain the long-lasting increase in GABA levels.…”
Section: Neurotransmitter Changes After Mcaosupporting
confidence: 86%
See 1 more Smart Citation
“…The permanent MCA ligation method which is also referred as pMCAo in the literature is used extensively as a focal ischemia model in rodents [1][2][3][4][5][6] . This method was originally described for rats by Tamura et al in 1981 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the clinical significance there has been a prolonged effort to develop suitable animal models to study the events that unfold during ischemic insult. These techniques include transient or permanent, focal or global ischemia models using many different animal models, with the most common being rodents.The permanent MCA ligation method which is also referred as pMCAo in the literature is used extensively as a focal ischemia model in rodents [1][2][3][4][5][6] . This method was originally described for rats by Tamura et al in 1981 7 .…”
mentioning
confidence: 99%